High prevalence of SARS-CoV-2 antibodies in care homes affected by COVID-19: Prospective cohort study, England. (November 2020) - Ladhani, Shamez N; Jeffery-Smith, Anna; Patel, Monika; Janarthanan, Roshni; Fok, Jonathan; Crawley-Boevey, Emma; Vusirikala, Amoolya; Fernandez Ruiz De Olano, Elena; Perez, Marina Sanchez; Tang, Suzanne; Dun-Campbell, Kate; Evans, Edward Wynne-; et al.
Abstract: Background: We investigated six London care homes experiencing a COVID-19 outbreak and found high rates of SARS-CoV-2 infection among residents and staff. Here we report follow-up investigations including antibody testing in the same care homes five weeks later. Methods: Residents and staff in the initial investigation had a repeat nasal swab for SARS-CoV-2 RT-PCR and a blood test for SARS CoV-2 antibodies using ELISA based on SARS-CoV-2 native viral antigens derived from infected cells and virus neutralisation. Findings: Of the 518 residents and staff in the initial investigation, 186/241 (77.2%) surviving residents and 208/254 (81.9%) staff underwent serological testing. Almost all SARS-CoV-2 RT-PCR positive residents and staff were seropositive five weeks later, whether symptomatic (residents 35/35, 100%; staff, 22/22, 100%) or asymptomatic (residents 32/33, 97.0%; staff 21/22, 95.5%). Symptomatic but SARS-CoV-2 RT-PCR negative residents and staff also had high seropositivity rates (residents 23/27, 85.2%; staff 18/21, 85.7%), as did asymptomatic RT-PCR negative individuals (residents 61/91, 67.0%; staff 95/143, 66.4%). Neutralising antibody was detected in 118/132 (89.4%) seropositive individuals and was not associated with age or symptoms. Ten residents (10/79 re-tested, 12.7%) remained RT-PCR positive but with higher RT-PCR cycle threshold values; 7/10 had serological testing and all were seropositive. New infections were detected in three residents and one staff. Interpretation: RT-PCR provides a point prevalence of SARS-CoV-2 infection but significantly underestimates total exposure in outbreak settings. In care homes experiencing large COVID-19 outbreaks, most residents and staff had neutralising SARS-CoV-2 antibodies, which was not associated with age or symptoms. Funding: PHE